Qui oblida lo passat oblida a si mateix: paremias in modern translations of Tirant lo Blanc - Robles Sabater, Ferran (Romanica Olomucensia, 2025)
This paper examines the translation of the paremias of the Catalan chivalric novel Tirant lo Blanc (1490) in four of its modern versions in German, French, English, and Italian. The research has a double purpose: on the one hand, it aims to determine what general strategy was followed in each version and how this is reflected in the choice of certain translation techniques; on the other hand, it intends to show the differences between the four texts. In order to achieve these goals, the 126 paremiological units contained in Books I and II of the novel were examined. Once each of the paragraphs containing the paremias had been transcribed and aligned with its translated versions, the translation technique used in each case was identified, as well as the type of correspondence generated between the original expression and the equivalence rendered in each of the target texts. The research that was carried out shows that all four versions share a general tendency to use neutralisation techniques (i.e. translating through non-paremiological constructions) and that the most frequent one is literal translation. To a lesser extent, paremiological equivalence is present in all four languages, although especially in the French version. The fidelity to the form pursued by the four versions becomes evident in a unique way in each of them and gives rise to divergences, ranging from the extreme literality of the Italian text to the great creativity of the German one.
Keywords: paremia; translation equivalence; translation techniques; paremiological translation; literary translation; chivalric novel